Groups for older people in residential and day-care: The other groupworkers - Bernard, Lorraine; Burton, John; Kyne, Phyllis; Simon, June (Groupwork, 2020)
The following article recounts the progress of four groups: a core group of workers on an in-service study course and three projects undertaken by course members in their work places with various groups of older people. We demonstrate the viability of groupwork by skilled, but not formally trained, basic grade staff: the uses of groups in a variety of residential and day care settings; the therapeutic use of groups in work with older people; the importance of support groups for groupworkers; the feasibility of groupwork even in social services settings which are badly understaffed and have an undeservedly low status; and the place of groupwork practice in social care teaching and training. The core group is part of the In-Service Course in Social Care at Southwark College and the groupwork projects were undertaken in a South London Borough. Publisher’s note: We are now putting all back issues of Groupwork on line. Articles in this issue have been scanned to pdf files as viable original typesetting files no longer exist. Though they may not look it, these files are searchable. This issue was published nearly 30 years ago. We have stated author professional details as received at time of publication. Abstracts are word-for-word transcriptions of the original abstracts with no attempt to update terminology.